Rhomboid proteases and their biological functions. - Freeman, M (2008)
The rhomboids are a well-conserved family of intramembrane serine proteases, which are unrelated to the classical soluble serine proteases. Their active site is buried within the plane of the membrane, and they cleave substrates in or near transmembrane domains. Although recently discovered, it is becoming clear that rhomboids control many important cellular functions. This review briefly describes recent biochemical and structural work that begins to explain how proteolysis occurs in a hydrophobic environment, but then focuses more extensively on the emerging biological functions of rhomboids. Although the function of most rhomboids is not yet known, they have already been implicated in growth factor signaling, mitochondrial function, host cell invasion by apicomplexan parasites, and protein translocation across membranes in bacteria. By exploiting cellular membrane trafficking machinery, rhomboids have evolved novel strategies to regulate proteolysis.